Identification of the area services provided by a pharmacist in the care of patients with mental health problems - conditions, care opportunities and patient needs - Bożena Karolewicz; Maciej Nowak; Agnieszka Gawin-Mikołajewicz; Piotr Milejski; Artur Owczarek (Polish Pharmaceutical Society, 2020)
Pharmacotherapy is the main treatment method for depression, bipolar disorder, and schizophrenia. As such, in many countries the potential service of pharmacist's, especially for medicine review, active participation in improving patient compliance, and cooperation with mental health clinical pharmacists, within an interdisciplinary healthcare team, are considered significant elements of healthcare. This article uses available references to identify the potential role and describe the types of activities undertaken by pharmacists as one of the groups of specialists supporting the healthcare of psychiatric patients. The participation of pharmacists in screening tests for example towards depression, their role in education, and delivering comprehensive information about medication to patients and other healthcare workers, their role in the improvement of primary prevention and health promotion as well as the participation in actions connected with changing patient's lifestyle have been described. Special attention was placed on the role of pharmacists in monitoring of pharmacotherapy with the goal to improve patient compliance on the use of antidepressants and participation in evaluation of laboratory test results and analysis of medication prescription in hospitals. Pharmacists should also consider/ take up pharmaceutical care of patients with psychiatric illnesses as an extended area of activity. The changing the attitude towards professional practice from a supplier of medicinal products to a specialist providing the best pharmacotherapy and safety for patients, will consequently increase the level of responsibility of pharmacies and pharmacists. This requires a change in perception of one's own role, an organizational and functional approach to exercising this area of pharmaceutical care. In addition, there is an urgent need to develop new standards, establish cooperation with other healthcare professions, and define strategies for the promotion/ marketing of pharmaceutical care. Restoration of the expected role of the pharmacy will be achieved only if pharmacists accept their social mandate to ensure safe and effective pharmacotherapy for individual patients, which was particularly presented in this paper for patients with mental health problems.